The Difference in Serum Pepsinogen I, Pepsinogen II, Carcinoembryonic Antigen, and Carcinoma Antigen 72-4 Levels between Children with and without Helicobacter Pylori Infection - Nasution, Iqbal Pahlevi Adeputra; Ruslie, Riska Habriel (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Helicobacter pylori (H. pylori) is a common infection in human. The infection is mainly acquired in childhood with global prevalence of 32.3%. Several markers such as pepsinogen I, pepsinogen II, carcinoembryonic antigen (CEA), and carcinoma antigen (CA) 72-4 are associated with H. pylori infection and its complications. OBJECTIVE: To determine the difference in serum pepsinogen I, pepsinogen II, CEA, and CA 72-4 levels in children with and without H. pylori infection. METHODS: A cross sectional study was conducted in Samosir Island, Indonesia. Inclusion criteria were children aged 2 to 18 years who did not take antibiotics, bismuth containing drugs, histamine-2 receptor antagonists, proton pump inhibitors, and immunomodulator for the last 4 weeks before the study. All subjects were divided into 2 groups: H. pylori positive and negative. Demographic and anthropometric data were gathered. Serum pepsinogen I, pepsinogen II, CEA, and CA 72-4 levels were evaluated. The differences were determined using Mann Whitney U-test. RESULTS: A total of 74 subjects were enrolled in this study. H. pylori positive and negative subjects were 38 and 36, respectively. Females were dominant in both groups. No difference was observed in gender, age, anthropometric characteristics, serum CEA level, and CA 72-4 level between both groups. Serum pepsinogen I and pepsinogen II levels were higher in H. pylori positive group compared to their counterparts (p= 0.013 and p= 0.001, respectively). CONCLUSION: There are significant differences in serum pepsinogen I and II levels between children with and without H. pylori infection.